2015
DOI: 10.4238/2015.february.13.16
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly and characterization of skin transcriptome using RNAseq in sheep (Ovis aries)

Abstract: ABSTRACT. Wool is produced via synthetic processes of wool follicles, which are embedded in the skin of sheep. The development of new-generation sequencing and RNA sequencing provides new approaches that may elucidate the molecular regulation mechanism of wool follicle development and facilitate enhanced selection for wool traits through gene-assisted selection or targeted gene manipulation. We performed de novo transcriptome sequencing of skin using the Illumina Hiseq 2000 sequencing system in sheep (Ovis ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…For example, several miRNAs (e.g., oar-miR-103-3p, oar-miR-148b-3p, oar-miR-320-3p, oar-miR-31-5p, oar-novel-1-5p, oar-novel-2-3p, miR-let-7, miR-199 and miR-200 families) were found to affect wool follicle development, and a large number of genes (e.g., KRTs, KRTAPs families, CST3, CSTB, S100A11, PPARD, CSTA, SIVA1, CCDC85B, FOXE1, VAX2, BAK1, ADRA1B, PKIA and HNF4A) were shown to be related to hair/ fleece development. In addition, earlier investigations indicated that several genes (e.g., DCT, MATP, TYR and TYRP1) played a central roles in coat color regulation and a few signaling pathways (Wnt, Jak-STAT, MAPK, Notch, TGF-β, Toll-like receptor and VEGF) were involved in the regulation of wool follicle bulb regression and regeneration [38][39][40][41] . Using Solexa sequencing (Illumina Genome Analyzer), Li et al identified 1910 known and 2261 novel mature miRNAs, and these miRNAs could have essential roles in telogen hair follicle development and growth, which are important for improving wool quality [77] .…”
Section: Wool Traitsmentioning
confidence: 99%
“…For example, several miRNAs (e.g., oar-miR-103-3p, oar-miR-148b-3p, oar-miR-320-3p, oar-miR-31-5p, oar-novel-1-5p, oar-novel-2-3p, miR-let-7, miR-199 and miR-200 families) were found to affect wool follicle development, and a large number of genes (e.g., KRTs, KRTAPs families, CST3, CSTB, S100A11, PPARD, CSTA, SIVA1, CCDC85B, FOXE1, VAX2, BAK1, ADRA1B, PKIA and HNF4A) were shown to be related to hair/ fleece development. In addition, earlier investigations indicated that several genes (e.g., DCT, MATP, TYR and TYRP1) played a central roles in coat color regulation and a few signaling pathways (Wnt, Jak-STAT, MAPK, Notch, TGF-β, Toll-like receptor and VEGF) were involved in the regulation of wool follicle bulb regression and regeneration [38][39][40][41] . Using Solexa sequencing (Illumina Genome Analyzer), Li et al identified 1910 known and 2261 novel mature miRNAs, and these miRNAs could have essential roles in telogen hair follicle development and growth, which are important for improving wool quality [77] .…”
Section: Wool Traitsmentioning
confidence: 99%
“…Recently, several studies have reported the successful transcriptome sequencing of multiple tissues in sheep brain 15 , uterus 16 , skeletal muscle 1719 , mammary gland 20 , milk 21 , rumen 22 , and skin 23 tissues. To the best of our knowledge, only two transcriptomic studies on sheep have recently been conducted on large intestine metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al . [7,8] performed de novo transcriptome sequencing of sheep skin and found fiber diameter was related to a few lipoic acid differentially expressed genes and antisense transcripts. However, no other studies have examined global gene expression in relation to wool fiber diameter.…”
Section: Introductionmentioning
confidence: 99%